Current Status and Challenges of Oncolytic Virotherapy for the Treatment of Glioblastoma - Mason J. Webb; Ugur Sener; Richard G. Vile (MDPI AG, 2023)
Despite decades of research and numerous clinical trials, the prognosis of patients diagnosed with glioblastoma (GBM) remains dire with median observed survival at 8 months. There is a critical need for novel treatments for GBM, which is the most common malignant primary brain tumor. Major advances in cancer therapeutics such as immune checkpoint inhibitors and chimeric antigen receptor (CAR) T-cell therapy have not yet led to improved outcomes for GBM. Conventional therapy of surgery followed by chemoradiation with or without tumor treating fields remains the standard of care. One of the many approaches to GBM therapy currently being explored is viral therapies. These typically work by selectively lysing target neoplastic cells, called oncolysis, or by the targeted delivery of a therapeutic transgene via a viral vector. In this review, we discuss the underlying mechanisms of action and describe both recent and current human clinical trials using these viruses with an emphasis on promising viral therapeutics that may ultimately break the field's current stagnant paradigm.